The Shift in the Value of Geuchik Leadership in Aceh: An Analysis of the Transition from Charismatic to Formal Leadership - Muliawati Darkasyi (Journal of Social and Policy Issues, 2026)
This study aims to analyze the shift in the value of Geuchik leadership in Aceh from a charismatic and culturally grounded model toward a formal and procedural model of village governance. In the traditional Acehnese gampong system, the Geuchik was not only an administrative leader but also a respected social, cultural, and religious figure whose authority was built on charisma, maturity, community trust, and mastery of local customs. This study employs a descriptive qualitative approach through observation, semi-structured interviews, and documentation, supported by a literature review and field data. The findings show that contemporary Geuchik selection increasingly prioritizes formal administrative requirements, such as age, educational certificates, and electoral procedures, rather than social stature, customary knowledge, and charismatic authority. This change has expanded democratic access to village leadership, including for younger and formally educated candidates. Still, it has also created a value gap between legal legitimacy and socio-cultural legitimacy. The decline of charismatic authority affects public respect, community compliance, dispute resolution, and the preservation of local wisdom. Therefore, the study argues that effective gampong leadership in Aceh requires a balance between formal governance capacity and culturally rooted leadership values.